Respuesta :
[tex](6x - 7) - (4 + 3x) = 13[/tex]
[tex]6x - 7 - 4 - 3x = 13[/tex]
[tex](6x - 3x) + ( - 7 - 4) = 13[/tex]
[tex]3x - 11 = 13[/tex]
[tex]3x = 13 + 11[/tex]
[tex]3x = 24[/tex]
[tex]x = \frac{24}{3} [/tex]
[tex]x = 8[/tex]
Step-by-step explanation:
Easy, remove the parenthesis
Since negative on positive is negative, it would be *underlined is changed equation*
6x-7- 4-3x=13
combine like terms
6x-3x=3x
3x= 13+7+4 (Bring all numbers that are not x's to the other side) *changed is underlined* *nubers become positive if on the other side in this situation*
Add: 13+7+4
13+7=20
20+4=24
3x=24
24 divided by 3x
(whole numbers always come first in dividing)
*ignore the x's in 3x*
24 divided by 3(x) is obviously 8
So x would be 8
x=8
Cheers! Mark brainliest if really useful :D